VULNERABILITIES IN CI-PLATFORMS THAT CAN BE EXPLOITED FOR CRYPTOCURRENCY MINING AND POSSIBLE SOLUTIONS TO THIS PROBLEM - Abdinurova, N.; Sokitbayev, M.; Suyerbassov, T.; Baimolda, A. (Journal of Emerging Technologies and Computing, 2021)
The topic of how vulnerabilities on CI-platforms that are subject to cryptocurrency mining is relevant. One solution is that the github has manually set the commit confirmation so that the cryptominer cannotautomate mining.